Sexually transmitted infection incidence among adolescents in Ireland. Issue 4 (10th June 2014) - Davoren, Martin P; Hayes, Kevin; Horgan, Mary; Shiely, Frances
Abstract : Objective: The burden of sexually transmitted infections (STIs) rests with young people, yet in Ireland there has been very little research into this population. The purpose of this study was to determine the incidence rate and establish risk factors that predict STI occurrence among adolescents in Ireland. Design: Routine diagnostic, demographic and behavioural data from first-time visits to three screening centres in the southwest of Ireland were obtained. Univariate and multivariable logistic regression models were used to assess risk factors that predict STI occurrence among adolescents. Results: A total of 2784 first-time patients, aged 13–19 years, received 3475 diagnoses between January 1999 and September 2009; 1168 (42%) of adolescents had notifiable STIs. The incidence rate of STIs is 225/100 000 person-years. Univariate analysis identified eligible risk factors ( p <0.2) for inclusion in the multivariable model. Multivariable logistic regression showed the dominant risk factors for STI diagnosis to be: males who sometimes [odds ratio (OR) 2.02] or never (OR 1.83) use condoms; and females 18–19 years (OR 2.26) and 16–18 years (OR 1.8), with 2 (OR 1.33) or 3+ (OR 1.56) partners in the last 12 months, who are non-intravenous drug users (OR 0.72), are most likely to receive a positive STI diagnosis. Conclusions: STI diagnosis has become increasingly common in Ireland. The proportion of notifications among those aged under 20 years is increasing. These data illustrate the significance of age, condom use and number of sexual partners as risk factors for STI diagnosis. Furthermore, providing data for the first time, we report on the high incidence rate of STIs among adolescents in Ireland. The high levels of risk-taking behaviour and STI acquisition are highlighted and suggest that there is a need for an integrated public health approach to combat this phenomenon in the adolescent population.